2018
DOI: 10.1038/s41598-018-31511-5
|View full text |Cite
|
Sign up to set email alerts
|

Searching the second hit in patients with inherited retinal dystrophies and monoallelic variants in ABCA4, USH2A and CEP290 by whole-gene targeted sequencing

Abstract: Inherited Retinal Dystrophies are clinically and genetically heterogeneous disorders affecting the photoreceptors. Although NGS has shown to be helpful for the molecular diagnosis of these conditions, some cases remain unsolved. Among these, several individuals harboured monoallelic variants in a recessive gene, suggesting that a comprehensive screening could improve the overall diagnosis. In order to assess the contribution of non-coding variations in a cohort of 29 patients, 25 of them with monoallelic mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…33 The new variant identified was a coding variant filtered out on the whole-exome sequencing analysis because of extremely low coverage. According to these data and findings from recent studies, 34 c.6148G>C should therefore be considered a likely benign variant. On the other hand, the frequent variant c.5603A>T, recently considered a low-penetrant variant, 18,19 was identified in 9 cases, allowing us to consider them solved, and only 2 carried an additional intronic variant in cis.…”
Section: We Report the Largest Cohort Of Patients Withmentioning
confidence: 54%
“…33 The new variant identified was a coding variant filtered out on the whole-exome sequencing analysis because of extremely low coverage. According to these data and findings from recent studies, 34 c.6148G>C should therefore be considered a likely benign variant. On the other hand, the frequent variant c.5603A>T, recently considered a low-penetrant variant, 18,19 was identified in 9 cases, allowing us to consider them solved, and only 2 carried an additional intronic variant in cis.…”
Section: We Report the Largest Cohort Of Patients Withmentioning
confidence: 54%
“…The shortage of some MLPA kits limited the detection of some CNVs, however the employment of QF‐PCR 38 or droplet digital PCR 39,40 may increase the detection rate of CNVs. Sanger sequencing, and the majority of NGS platforms are limited in their ability to detect CNVs, nevertheless, some genes involving PRPF31 and USH2A do have a high percentage of CNV variants 41‐43 . In our study, HEDEP achieved a sequencing depth of up to ×800.…”
Section: Discussionmentioning
confidence: 64%
“…A specific panel of genes will allow the study of known IRD at a high time/effectiveness ratio regardless of the clinical diagnosis, which is an advantage in those cases in which the clinical diagnosis is not well defined or overlaps between different clinical entities. Furthermore, it allows not only the possibility of including a greater number of probes in repetitive regions such as ORF15 of the RPGR gene, which is highly involved in X-linked IRD cases ( Vervoort et al, 2000 ; Megaw et al, 2015 ; Chiang et al, 2018 ; Charng et al, 2019 ), but also reported deep-intronic pathogenic variants ( González-del Pozo et al, 2018 ; Di Scipio et al, 2020 ). On the other hand, WES made it possible to find mutations in novel IRD-related genes without updating the panel in low prevalent genes not included for the sake of increasing the depth of coverage or to identify novel IRD genes.…”
Section: Discussionmentioning
confidence: 99%